2018
DOI: 10.1101/295618
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A stimulus artefact undermines the evidence for independent ON and OFF channels in stereopsis

Abstract: Early vision proceeds through distinct ON and OFF channels, which encode luminance increments and decrements respectively. It has been argued that these channels also contribute separately to stereoscopic vision. This is based on the fact that observers perform better on a noisy disparity discrimination task when the stimulus is a random-dot pattern consisting of equal numbers of black and white dots (a "mixed-polarity stimulus", argued to activate both ON and OFF stereo channels), than when it consists of all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…Alternatively, the benefit could be explained by different image statistics of mixed- and single-contrast polarity RDSs. Read and Cumming (2018) showed that stimuli used in this study and all previous studies contain higher interocular image correlation at the target disparity if they have mixed contrast polarity compared to a single contrast polarity. A more correlated input drives binocular cells in primary visual cortex more strongly and produces a more reliable binocular disparity signal.…”
Section: Discussionmentioning
confidence: 50%
“…Alternatively, the benefit could be explained by different image statistics of mixed- and single-contrast polarity RDSs. Read and Cumming (2018) showed that stimuli used in this study and all previous studies contain higher interocular image correlation at the target disparity if they have mixed contrast polarity compared to a single contrast polarity. A more correlated input drives binocular cells in primary visual cortex more strongly and produces a more reliable binocular disparity signal.…”
Section: Discussionmentioning
confidence: 50%
“…Depth judgements are more accurate when binocular images are composed of both light and dark features, rather than just one or the other (Harris & Parker, 1995;Read, Vaz, & Serrano-Pedraza, 2011). This finding was initially interpreted as evidence of separate ON and OFF binocular channels; however, contradictory physiological (Schiller, 1992), behavioural (Read et al, 2011) and theoretical (Goncalves & Welchman, 2017;Read & Cumming, 2018) evidence has cast doubt on this hypothesis. Here we tested the potential for changes in the balance of excitation and inhibition that are produced by viewing these single-and mixed-polarity random-dot stereograms (RDS).…”
Section: Discussionmentioning
confidence: 99%
“…Critically, this neural network also reproduced the mixedpolarity benefit, suggesting that the difference in positive/negative activity may underlie this puzzling phenomenon. Read and Cumming (2018) have proposed that the mixed-polarity benefit arises from subtle changes in image correlation under some restricted circumstances. Given that the image correlation was the same between single-and mixed-polarity conditions, the difference in neurotransmitter concentration cannot be attributed to this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations